Effect of a new cross-linked hyaluronan gel on the staple line after sleeve gastrectomy in a rat model - Bülbüller,Nurullah (2018)
Abstract Purpose: To evaluate the effect of a new cross-linked hyaluronan (NCHA) gel on healing of the staple line in an experimental sleeve gastrectomy. Methods: Eighteen rats were randomly divided into three groups. The control group (n = 6) received no medication. In the saline group (n = 6) and NCHA gel group (n = 6), saline and NCHA gel were respectively administered onto the staple line and intraperitoneally into the abdominal cavity after the standard stapling procedure. Results: The fibroblast activity and collagen deposition were significantly higher in the NCHA gel group than in the control group (p = 0.00, p = 0.017) and saline group (p = 0.004, p = 0.015). The tissue hydroxyproline protein level was significantly higher in the NCHA gel group than in the control group (p = 0.041). Adhesion formation was significantly lower in the NCHA gel group than in the control and saline groups (p = 0.015, p = 0.041). Conclusions: New cross-linked hyaluronan gel could be an effective approach to improve staple line wound healing and prevent potential leakage after sleeve gastrectomy. Moreover, NCHA gel helps to prevent adhesion formation without compromising healing of the staple line.